A coating slurry resistant to high temperature steam oxidation, a coating and a preparation method thereof

By using high-temperature water vapor oxidation coating slurry composed of aluminum powder, silicon powder, alumina powder and MXene materials, the problem of oxidation of austenitic steel for boilers in the high-temperature water vapor environment in the prior art is solved, and the problem of oxidation of austenitic steel for boilers in high-temperature water vapor environment is achieved. The coating has efficient anti-oxidation and crack resistance, extending the service life of the boiler.

CN119119786BActive Publication Date: 2025-02-14XIAN THERMAL POWER RES INST CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411586199.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent the oxidation of austenitic steel for boilers in high-temperature water vapor environments, resulting in a decrease in heat exchange efficiency and an increase in the risk of pipeline blockage.

Method used

Using high-temperature water vapor oxidation coating slurry composed of aluminum powder, silicon powder, alumina powder, MXene material and aluminum dihydrogen phosphate solution, the coating is formed by ball mill mixing and heat treatment, which improves the crack resistance of the coating and Antioxidant properties.

Benefits of technology

It delays the oxidation process of high-temperature water vapor on the substrate, improves the oxidation performance of the substrate against high-temperature water vapor, reduces the risk of cracks and peeling of the coating, and thus extends the service life of the boiler.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119786B_ABST
    Figure CN119119786B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of material surface coatings, and provides a coating slurry resistant to high-temperature steam oxidation, a coating and a preparation method thereof. The coating slurry resistant to high-temperature steam oxidation is obtained by mixing a solid phase component and a liquid phase component in a ratio of 10g: (3-7) mL; by mass, the solid phase component includes: 50-60 parts of aluminum powder, 5-15 parts of silicon powder, 10-20 parts of aluminum oxide powder, and 5-35 parts of MXene material; the liquid phase component includes aluminum dihydrogen phosphate solution, chromium trioxide and water glass; wherein the ratio of aluminum dihydrogen phosphate solution, chromium trioxide and water glass is 100mL: (10-30) g: (5-15) mL. A coating is prepared based on the above coating, and the present invention improves the crack resistance and high-temperature steam oxidation resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface coatings, and in particular relates to a coating slurry resistant to high-temperature steam oxidation, a coating and a preparation method thereof. Background Art

[0002] In thermal power units, boilers operate in a high-temperature environment. With the development of ultra-supercritical power generation technology, the temperature and pressure of water vapor in the boiler continue to increase, causing the inner wall of the boiler to be oxidized by water vapor to form an oxide layer. The formation of the oxide layer will reduce the effective contact area between the heating surface of the inner wall of the boiler and the water vapor, thereby reducing the heat exchange efficiency; the peeling of the oxide layer may block the pipeline, resulting in obstruction of the flow of water vapor in the pipeline, and then causing over-temperature pipe burst.

[0003] There are two ways to improve the steam oxidation resistance of austenitic steel for boilers in the prior art. One is to refine the grains, and the other is to shot peen the inner wall. These two methods can enable austenitic steel to quickly grow a protective Cr2O3 film, which has antioxidant properties. However, in water vapor above 600°C, Cr2O3 has poor stability and is easy to peel off, which will further increase the risk of pipe blockage and burst. In addition, as the service time increases, the Cr content in austenitic steel will not be able to meet the needs of growing the Cr2O3 film, resulting in an accelerated decrease in the oxidation resistance of the boiler. Therefore, these two methods can only improve the oxidation resistance in the early stage and cannot fundamentally solve the problem.

[0004] In order to further solve the oxidation problem, high temperature steam oxidation resistant coating technology came into being. High temperature steam oxidation resistant coating is a special coating used to protect the substrate from oxidation in a high temperature steam environment. It can prevent the substrate from being oxidized and corroded in a high temperature steam environment and extend the service life of the substrate.

[0005] Among them, silicon-modified aluminide coating is one of the high-temperature steam oxidation resistant coatings. However, due to the large difference in thermal expansion coefficient between the aluminide coating and the substrate, a large stress is generated during the start-up and shutdown of the boiler, which makes the coating prone to cracks or even peeling. In addition, the high-temperature steam oxidation resistance of existing silicon-modified aluminide coatings needs to be improved. Summary of the invention

[0006] In order to solve the above problems of the prior art, the present invention provides a coating slurry resistant to high temperature steam oxidation, a coating and a preparation method thereof, which improve the coating's crack resistance and high temperature steam oxidation resistance.

[0007] The present invention is achieved through the following technical solutions:

[0008] The present invention provides a coating slurry resistant to high-temperature steam oxidation. The coating slurry is obtained by mixing a solid phase component and a liquid phase component in a ratio of 10 g: (3-7) mL; the solid phase component comprises, by mass, 50-60 parts of aluminum powder, 5-15 parts of silicon powder, 10-20 parts of aluminum oxide powder, and 5-35 parts of MXene material; the liquid phase component comprises aluminum dihydrogen phosphate solution, chromium trioxide and water glass; wherein the ratio of aluminum dihydrogen phosphate solution, chromium trioxide and water glass is 100 mL: (10-30) g: (5-15) mL.

[0009] Preferably, the solid phase components include, by weight: 50 to 60 parts of aluminum powder, 5 to 15 parts of silicon powder, 10 to 20 parts of alumina powder, and 15 to 25 parts of MXene material.

[0010] Preferably, the MXene material is multilayer Ti2CT x MXene powder, multilayer Nb2CT x MXene powder or multilayer Mo2CT x MXene powder.

[0011] The method for preparing the coating slurry resistant to high temperature steam oxidation of the present invention comprises:

[0012] (1) Aluminum powder, silicon powder, alumina powder, and MXene powder are ball-milled to obtain a solid phase component;

[0013] (2) adding chromium trioxide to aluminum dihydrogen phosphate solution, stirring until dissolved, then adding water glass, stirring to obtain a liquid phase component;

[0014] (3) The solid phase components and the liquid phase components are mixed and ball-milled to obtain a coating slurry.

[0015] Preferably, the ball milling in step (1) is wet ball milling, and the solvent used in the wet ball milling is ethanol.

[0016] The present invention also provides a coating resistant to high temperature steam oxidation, which is prepared by coating the above-mentioned coating resistant to high temperature steam oxidation slurry on a substrate.

[0017] Preferably, the substrate is boiler steel, such as austenitic steel.

[0018] The method for preparing the coating resistant to high temperature steam oxidation of the present invention comprises:

[0019] (1) applying the coating slurry to the surface of a substrate and drying it to form a coating precursor on the substrate;

[0020] (2) curing the coating precursor;

[0021] (3) Under argon protection, the cured coating precursor is heat treated to obtain a coating.

[0022] Preferably, in the method for preparing the coating resistant to high temperature steam oxidation, before step (1), the substrate is pretreated by cleaning, drying, and then preheating the substrate surface.

[0023] Preferably, in the method for preparing the coating resistant to high temperature steam oxidation, in step (2), the curing temperature is 300-400° C., and the curing time is 30-50 min.

[0024] Preferably, in the method for preparing the coating resistant to high temperature steam oxidation, in step (3), the heat treatment temperature is 900-1100° C. and the time is 10-20 min.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention adds MXene material to the coating slurry. MXene material is a type of two-dimensional material with a graphene-like structure. After the coating slurry forms a coating, the two-dimensional structure of the MXene material can increase the diffusion path of water vapor in the coating, thereby delaying the oxidation process of the substrate by high-temperature water vapor and improving the substrate's resistance to high-temperature water vapor oxidation. In addition, the lamella structure of the MXene material can cause the deflection of cracks, causing the cracks to change direction during the expansion process. This deflection process consumes more energy, so it can effectively inhibit the expansion speed of the cracks; the boundaries of the MXene material lamellae can effectively hinder the movement of dislocations. By hindering the movement of dislocations, the MXene material lamella structure can reduce the generation and expansion of cracks; therefore, the lamella structure of the MXene material can improve the crack resistance of the coating and prevent the coating from breaking and falling off.

[0027] Furthermore, the present invention optimizes the amount of MXene material added through research. When 15 to 25 parts of MXene material are added to the solid phase component, the resistance to high-temperature steam oxidation is better. Too low or too high an amount of MXene material added is not conducive to improving the resistance to high-temperature steam oxidation. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a cross-sectional morphology diagram of the coating prepared in Example 3 of the present invention.

[0029] Figure 2 This is a cross-sectional morphology of the coating after the thermal shock test of the sample in Example 3 of the present invention.

[0030] Figure 3 This is a cross-sectional morphology of the coating after the thermal shock test of the sample of comparative example 1 of the present invention. DETAILED DESCRIPTION

[0031] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0032] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0033] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0034] The coating slurry resistant to high-temperature steam oxidation of the present invention is obtained by mixing a solid phase component and a liquid phase component in a ratio of 10g: (3-7) mL; the solid phase component comprises, by mass, 50-60 parts of aluminum powder, 5-15 parts of silicon powder, 10-20 parts of aluminum oxide powder, and 5-35 parts of MXene material; the liquid phase component comprises aluminum dihydrogen phosphate solution, chromium trioxide and water glass; wherein the ratio of aluminum dihydrogen phosphate solution, chromium trioxide and water glass is 100 mL: (10-30) g: (5-15) mL.

[0035] MXene materials are a type of two-dimensional materials with a graphene-like structure. When MXene materials are applied to the coating of the present invention, the two-dimensional structure of the MXene material can increase the diffusion path of water vapor in the coating, thereby delaying the oxidation process of the substrate by high-temperature water vapor, thereby improving the overall resistance of the substrate to high-temperature water vapor oxidation. In addition, the two-dimensional structure of the MXene material can also improve the crack resistance of the coating and prevent the coating from breaking and falling off. This is because the layered structure of the MXene material gives the coating a certain degree of mechanical flexibility and ductility, thereby improving the crack resistance of the coating.

[0036] In some specific embodiments of the present invention, the MXene material is a multilayer Ti2CT x MXene powder, multilayer Nb2CT xMXene powder or multilayer Mo2CT x MXene powder.

[0037] In the present invention, the concentration of the aluminum dihydrogen phosphate solution can be 20% to 50%. The concentration of the aluminum dihydrogen phosphate solution used in the embodiment of the present invention is 25%.

[0038] The method for preparing the coating slurry resistant to high temperature steam oxidation of the present invention comprises:

[0039] (1) Preparation of solid phase components: aluminum powder, silicon powder, alumina powder, and MXene powder are ball-milled to obtain solid phase components;

[0040] (2) Preparation of liquid phase component: add chromium trioxide to aluminum dihydrogen phosphate solution, stir until completely dissolved, then add water glass, stir to obtain liquid phase component;

[0041] (3) Preparation of coating slurry: The solid phase components and the liquid phase components are mixed and ball milled to obtain the coating slurry.

[0042] The present invention also provides a coating resistant to high temperature steam oxidation, the preparation method of which comprises:

[0043] (1) applying the coating slurry to the surface of a substrate and drying it to form a coating precursor on the substrate;

[0044] (2) curing the coating precursor;

[0045] (3) Under argon protection, the cured coating precursor is heat treated to obtain a coating.

[0046] In some specific embodiments of the present invention, the substrate is pretreated in advance: the surface of the substrate is cleaned, dried, and then preheated.

[0047] The cleaning method may include: firstly flushing the substrate with a high-pressure water gun, and then cleaning with alcohol.

[0048] The preheating is specifically: preheating at 200-250° C. for 10-20 min, preferably preheating at 220° C. for 15 min.

[0049] In some specific embodiments of the present invention, in step (2), the curing temperature is 300-400° C., and the curing time is 30-50 min.

[0050] In some specific embodiments of the present invention, in step (3), the heat treatment temperature is 900-1100° C., and the time is 10-20 min.

[0051] The coating resistant to high temperature steam oxidation of the present invention is used for corrosion protection of the inner wall of boiler flow components in thermal power units, and the substrate is boiler steel, such as austenitic steel.

[0052] The samples used in the following examples and comparative examples of the present invention are austenitic steel Super304H, and the MXene materials used are purchased from Xi'an Qiyue Biotechnology Co., Ltd.

[0053] Example 1

[0054] Step 1, preparation of coating slurry:

[0055] (1) Preparation of solid phase components: Weigh 55 parts of aluminum powder, 10 parts of silicon powder, 15 parts of alumina powder, and 5 parts of multilayer Ti2CT x MXene powder, add the weighed material into a ball mill, add solvent ethanol, ball mill for 3 hours at a speed of 500r / min, and dry to obtain a solid phase component; wherein the diameters of the zirconium oxide balls used in the ball milling are Φ5 and Φ10, and the mass ratio of the Φ5 and Φ10 zirconium oxide balls is 7:3;

[0056] (2) Preparation of liquid phase component: Take 100 mL of 25% aluminum dihydrogen phosphate solution, place it in a 90°C water bath, add 15 g of chromium trioxide to the aluminum dihydrogen phosphate solution, stir until completely dissolved, then add 10 mL of water glass, stir thoroughly and filter the residue to obtain the liquid phase component;

[0057] (3) Preparation of coating slurry: The solid phase component and the liquid phase component were stirred and mixed for 2 h at a solid-liquid ratio of 10 g:5 mL, and then ball milled for 3 h to obtain a coating slurry.

[0058] Step 2, coating preparation:

[0059] (1) Sample surface pretreatment: First rinse the sample with a high-pressure water gun, then clean it with alcohol, dry it at 80°C for 15 minutes, and then preheat it at 220°C for 15 minutes;

[0060] (2) Application of coating slurry: The coating slurry prepared above was evenly applied on the surface of the sample and allowed to air dry for 24 h;

[0061] (3) Curing of the coating: The sample obtained in step (2) was cured at 350°C for 40 min;

[0062] (4) Heat treatment: The sample obtained in step (3) was heated at 1000°C for 15 min under argon protection to obtain a coating.

[0063] Example 2

[0064] Step 1, preparation of coating slurry:

[0065] (1) Preparation of solid phase components: Weigh 55 parts of aluminum powder, 10 parts of silicon powder, 15 parts of alumina powder, and 15 parts of multilayer Ti2CT x MXene powder, add the weighed material into a ball mill, add solvent ethanol, ball mill for 3 hours at a speed of 500r / min, and dry to obtain a solid phase component; wherein the diameters of the zirconium oxide balls used in the ball milling are Φ5 and Φ10, and the mass ratio of the Φ5 and Φ10 zirconium oxide balls is 7:3;

[0066] (2) Preparation of liquid phase component: Take 100 mL of 25% aluminum dihydrogen phosphate solution, place it in a 90°C water bath, add 15 g of chromium trioxide to the aluminum dihydrogen phosphate solution, stir until completely dissolved, then add 10 mL of water glass, stir thoroughly and filter the residue to obtain the liquid phase component;

[0067] (3) Preparation of coating slurry: The solid phase component and the liquid phase component were stirred and mixed for 2 h at a solid-liquid ratio of 10 g:5 mL, and then ball milled for 3 h to obtain a coating slurry.

[0068] Step 2, coating preparation:

[0069] (1) Sample surface pretreatment: First rinse the sample with a high-pressure water gun, then clean it with alcohol, dry it at 80°C for 15 minutes, and then preheat it at 220°C for 15 minutes;

[0070] (2) Application of coating slurry: The coating slurry prepared above was evenly applied on the surface of the sample and allowed to air dry for 24 h;

[0071] (3) Curing of the coating: The sample obtained in step (2) was cured at 350°C for 40 min;

[0072] (4) Heat treatment: The sample obtained in step (3) was heated at 1000°C for 15 min under argon protection to obtain a coating.

[0073] Example 3

[0074] Step 1, preparation of coating slurry:

[0075] (1) Preparation of solid phase components: Weigh 55 parts of aluminum powder, 10 parts of silicon powder, 15 parts of alumina powder, and 20 parts of multilayer Ti2CT x MXene powder, add the weighed material into a ball mill, add solvent ethanol, ball mill for 3 hours at a speed of 500r / min, and dry to obtain a solid phase component; wherein the diameters of the zirconium oxide balls used in the ball milling are Φ5 and Φ10, and the mass ratio of the Φ5 and Φ10 zirconium oxide balls is 7:3;

[0076] (2) Preparation of liquid phase component: Take 100 mL of 25% aluminum dihydrogen phosphate solution, place it in a 90°C water bath, add 15 g of chromium trioxide to the aluminum dihydrogen phosphate solution, stir until completely dissolved, then add 10 mL of water glass, stir thoroughly and filter the residue to obtain the liquid phase component;

[0077] (3) Preparation of coating slurry: The solid phase component and the liquid phase component were stirred and mixed for 2 h at a solid-liquid ratio of 10 g:5 mL, and then ball milled for 3 h to obtain a coating slurry.

[0078] Step 2, coating preparation:

[0079] (1) Sample surface pretreatment: First rinse the sample with a high-pressure water gun, then clean it with alcohol, dry it at 80°C for 15 minutes, and then preheat it at 220°C for 15 minutes;

[0080] (2) Application of coating slurry: The coating slurry prepared above was evenly applied on the surface of the sample and allowed to air dry for 24 h;

[0081] (3) Curing of the coating: The sample obtained in step (2) was cured at 350°C for 40 min;

[0082] (4) Heat treatment: The sample obtained in step (3) was kept at 1000°C for 15 min under argon protection to obtain a coating (such as Figure 1 as shown).

[0083] Example 4

[0084] Step 1, preparation of coating slurry:

[0085] (1) Preparation of solid phase components: Weigh 55 parts of aluminum powder, 10 parts of silicon powder, 15 parts of alumina powder, and 25 parts of multilayer Ti2CT x MXene powder, add the weighed material into a ball mill, add solvent ethanol, ball mill for 3 hours at a speed of 500r / min, and dry to obtain a solid phase component; wherein the diameters of the zirconium oxide balls used in the ball milling are Φ5 and Φ10, and the mass ratio of the Φ5 and Φ10 zirconium oxide balls is 7:3;

[0086] (2) Preparation of liquid phase component: Take 100 mL of 25% aluminum dihydrogen phosphate solution, place it in a 90°C water bath, add 15 g of chromium trioxide to the aluminum dihydrogen phosphate solution, stir until completely dissolved, then add 10 mL of water glass, stir thoroughly and filter the residue to obtain the liquid phase component;

[0087] (3) Preparation of coating slurry: The solid phase component and the liquid phase component were stirred and mixed for 2 h at a solid-liquid ratio of 10 g:5 mL, and then ball milled for 3 h to obtain a coating slurry.

[0088] Step 2, coating preparation:

[0089] (1) Sample surface pretreatment: First rinse the sample with a high-pressure water gun, then clean it with alcohol, dry it at 80°C for 15 minutes, and then preheat it at 220°C for 15 minutes;

[0090] (2) Application of coating slurry: The coating slurry prepared above was evenly applied on the surface of the sample and allowed to air dry for 24 h;

[0091] (3) Curing of the coating: The sample obtained in step (2) was cured at 350°C for 40 min;

[0092] (4) Heat treatment: The sample obtained in step (3) was heated at 1000°C for 15 min under argon protection to obtain a coating.

[0093] Example 5

[0094] Step 1, preparation of coating slurry:

[0095] (1) Preparation of solid phase components: Weigh 55 parts of aluminum powder, 10 parts of silicon powder, 15 parts of alumina powder, and 35 parts of multilayer Ti2CT x MXene powder, add the weighed material into a ball mill, add solvent ethanol, ball mill for 3 hours at a speed of 500r / min, and dry to obtain a solid phase component; wherein the diameters of the zirconium oxide balls used in the ball milling are Φ5 and Φ10, and the mass ratio of the Φ5 and Φ10 zirconium oxide balls is 7:3;

[0096] (2) Preparation of liquid phase component: Take 100 mL of 25% aluminum dihydrogen phosphate solution, place it in a 90°C water bath, add 15 g of chromium trioxide to the aluminum dihydrogen phosphate solution, stir until completely dissolved, then add 10 mL of water glass, stir thoroughly and filter the residue to obtain the liquid phase component;

[0097] (3) Preparation of coating slurry: The solid phase component and the liquid phase component were stirred and mixed for 2 h at a solid-liquid ratio of 10 g:5 mL, and then ball milled for 3 h to obtain a coating slurry.

[0098] Step 2, coating preparation:

[0099] (1) Sample surface pretreatment: First rinse the sample with a high-pressure water gun, then clean it with alcohol, dry it at 80°C for 15 minutes, and then preheat it at 220°C for 15 minutes;

[0100] (2) Application of coating slurry: The coating slurry prepared above was evenly applied on the surface of the sample and allowed to air dry for 24 h;

[0101] (3) Curing of the coating: The sample obtained in step (2) was cured at 350°C for 40 min;

[0102] (4) Heat treatment: The sample obtained in step (3) was heated at 1000°C for 15 min under argon protection to obtain a coating.

[0103] Example 6

[0104] Step 1, preparation of coating slurry:

[0105] (1) Preparation of solid phase components: Weigh 50 parts of aluminum powder, 15 parts of silicon powder, 20 parts of alumina powder, and 20 parts of multilayer Nb2CT x MXene powder, add the weighed material into a ball mill, add solvent ethanol, ball mill for 3 hours at a speed of 500r / min, and dry to obtain a solid phase component; wherein the diameters of the zirconium oxide balls used in the ball milling are Φ5 and Φ10, and the mass ratio of the Φ5 and Φ10 zirconium oxide balls is 7:3;

[0106] (2) Preparation of liquid phase component: Take 100 mL of 25% aluminum dihydrogen phosphate solution, place it in a 90°C water bath, add 10 g of chromium trioxide to the aluminum dihydrogen phosphate solution, stir until completely dissolved, then add 15 mL of water glass, stir thoroughly and filter the residue to obtain the liquid phase component;

[0107] (3) Preparation of coating slurry: The solid phase component and the liquid phase component were stirred and mixed for 2 h at a solid-liquid ratio of 10 g:3 mL, and then ball milled for 3 h to obtain a coating slurry.

[0108] Step 2, coating preparation:

[0109] (1) Sample surface pretreatment: First rinse the sample with a high-pressure water gun, then clean it with alcohol, dry it at 80°C for 15 minutes, and then preheat it at 220°C for 15 minutes;

[0110] (2) Application of coating slurry: The coating slurry prepared above was evenly applied on the surface of the sample and allowed to air dry for 24 h;

[0111] (3) Curing of the coating: Curing the sample obtained in step (2) at 400°C for 30 min;

[0112] (4) Heat treatment: The sample obtained in step (3) was kept at 1100°C for 10 min under argon protection to obtain a coating.

[0113] Example 7

[0114] Step 1, preparation of coating slurry:

[0115] (1) Preparation of solid phase components: weigh 60 parts of aluminum powder, 5 parts of silicon powder, 10 parts of alumina powder, and 20 parts of multilayer Mo2CT x MXene powder, add the weighed material into a ball mill, add solvent ethanol, ball mill for 3 hours at a speed of 500r / min, and dry to obtain a solid phase component; wherein the diameters of the zirconium oxide balls used in the ball milling are Φ5 and Φ10, and the mass ratio of the Φ5 and Φ10 zirconium oxide balls is 7:3;

[0116] (2) Preparation of liquid phase component: Take 100 mL of 25% aluminum dihydrogen phosphate solution, place it in a 90°C water bath, add 30 g of chromium trioxide to the aluminum dihydrogen phosphate solution, stir until completely dissolved, then add 5 mL of water glass, stir thoroughly and filter the residue to obtain the liquid phase component;

[0117] (3) Preparation of coating slurry: The solid phase component and the liquid phase component were stirred and mixed for 2 h at a solid-liquid ratio of 10 g:7 mL, and then ball milled for 3 h to obtain a coating slurry.

[0118] Step 2, coating preparation:

[0119] (1) Sample surface pretreatment: First rinse the sample with a high-pressure water gun, then clean it with alcohol, dry it at 80°C for 15 minutes, and then preheat it at 220°C for 15 minutes;

[0120] (2) Application of coating slurry: The coating slurry prepared above was evenly applied on the surface of the sample and allowed to air dry for 24 h;

[0121] (3) Curing of the coating: Curing the sample obtained in step (2) at 300°C for 50 min;

[0122] (4) Heat treatment: The sample obtained in step (3) was heated at 900°C for 20 min under argon protection to obtain a coating.

[0123] Comparative Example 1

[0124] The difference from Example 3 is that no multilayer Ti2CT is added to the solid phase component. x MXene powder.

[0125] Comparative Example 2

[0126] The difference from Example 3 is that 50 parts of multilayer Ti2CT x MXene powder.

[0127] The coatings obtained in each embodiment and comparative example were tested for their anti-water vapor oxidation performance at test temperatures of 600° C. and 650° C., respectively. The test results are shown in Tables 1 and 2.

[0128] Table 1. Sample mass change data in 600℃ water vapor (mg / cm 2 )

[0129]

[0130] Table 2 Sample mass change data in 650℃ water vapor (mg / cm 2 )

[0131]

[0132] As can be seen from Table 1 and Table 2, compared with the samples without coating, the mass changes of the samples of Examples 1 to 7 and Comparative Examples 1 to 2 coated with coatings are all reduced, indicating that the coating has a certain anti-water vapor oxidation effect. Compared with Comparative Example 1 without adding MXene, the mass changes of the samples of Examples 1 to 7 of the present invention are all reduced, indicating that the addition of MXene can further improve the anti-water vapor oxidation effect of the samples. This is because the layered structure of MXene increases the diffusion path of water vapor, thereby slowing down the oxidation process of water vapor on the sample matrix.

[0133] Comparison of Examples 1 to 5 shows that in the multilayer Ti2CT x When the addition amount of MXene powder is less than 20 parts, the anti-water vapor oxidation effect of the sample coating decreases with the increase of the multilayer Ti2CT x The increase in the amount of MXene powder added gradually increases. x When the addition amount of MXene powder exceeds 20 parts, the anti-water vapor oxidation effect of the sample coating decreases with the increase of multilayer Ti2CT x The increase in the amount of MXene powder added gradually decreases, indicating that the multilayer Ti2CT x The addition amount of MXene powder has a certain influence on the anti-water vapor oxidation effect of the sample coating. x When the amount of MXene powder added is low, its effect is weak, while when it is added in a large amount, it will affect the density of the coating and weaken the antioxidant effect. x MXene powder, resulting in a significant weakening of the anti-water vapor oxidation effect. x The addition amount of MXene powder should be controlled at 20 parts.

[0134] According to the thermal shock test standard of Shanghai Boiler Factory, the thermal shock performance test of the coating was carried out under the condition of 700℃ / 10min, and the number of thermal shock cycles was 30. The results are as follows: Figure 2 and 3 shown.

[0135] like Figure 2As shown in FIG. 1 , after 30 thermal shock cycles, the coating of the sample of Example 3 of the present invention is basically intact, and no cracks are observed under microscopic observation; Figure 3 As shown, the coating of the sample of comparative example 1 without adding MXene has slight cracks. This is because the layered structure of MXene makes the coating have certain mechanical flexibility and ductility, thereby improving the crack resistance of the coating.

Claims

1. A coating slurry resistant to high temperature steam oxidation, characterized in that: The coating slurry is obtained by mixing a solid phase component and a liquid phase component in a ratio of 10 g: (3-7) mL; The solid phase components include, by weight: 50-60 parts of aluminum powder, 5-15 parts of silicon powder, 10-20 parts of alumina powder, and 15-25 parts of MXene material; The liquid phase components include aluminum dihydrogen phosphate solution, chromium trioxide and water glass; wherein the ratio of aluminum dihydrogen phosphate solution, chromium trioxide and water glass is 100 mL: (10-30) g: (5-15) mL.

2. The coating slurry resistant to high temperature steam oxidation according to claim 1, characterized in that: The MXene material is a multilayer Ti2CT x MXene powder, multilayer Nb2CT x MXene powder or multilayer Mo2CT x MXene powder.

3. The method for preparing the coating slurry resistant to high temperature steam oxidation according to any one of claims 1 to 2, characterized in that: include: (1) ball milling aluminum powder, silicon powder, alumina powder and MXene powder to obtain a solid phase component; (2) adding chromium trioxide to aluminum dihydrogen phosphate solution, stirring until dissolved, then adding water glass, stirring to obtain a liquid phase component; (3) The solid phase components and the liquid phase components are mixed and ball-milled to obtain a coating slurry.

4. The method for preparing a coating slurry resistant to high temperature steam oxidation according to claim 3, characterized in that: The ball milling in step (1) is wet ball milling, and the solvent used in the wet ball milling is ethanol.

5. A coating resistant to high temperature steam oxidation, characterized in that: The coating slurry resistant to high temperature steam oxidation according to any one of claims 1 to 2 is coated on a substrate to obtain the coating.

6. The high temperature steam oxidation resistant coating according to claim 5, characterized in that: The substrate is boiler steel.

7. The method for preparing the coating resistant to high temperature steam oxidation according to claim 5, characterized in that: include: (1) applying the coating slurry to the surface of a substrate and drying it to form a coating precursor on the substrate; (2) curing the coating precursor; (3) Under argon protection, the cured coating precursor is heat treated to obtain a coating.

8. The method for preparing a coating resistant to high temperature steam oxidation according to claim 7, characterized in that: In step (2), the curing temperature is 300-400°C and the curing time is 30-50 minutes.

9. The method for preparing a coating resistant to high temperature steam oxidation according to claim 7, characterized in that: In step (3), the heat treatment temperature is 900-1100°C and the time is 10-20 min.

Citation Information

Patent Citations

  • Preparation method of obdurability high-temperature steam oxidation resistant coating

    CN113802088A

  • Mxene modified water-based inorganic zinc-rich anti-skid and anti-corrosion coating

    CN117089231A